'Dalit Feminist Theory: A Reader' - Preeti . (Caste, 2023)
This reader is a compilation of eighteen essays written by academics, feminists and scholar-activists from a Dalit Feminist Perspective. The editors Sunaina Arya and Aakash Singh Rathore, introduces the book by theorizing Dalit feminism underpinning its ontology and epistemology. Critiquing the academic discourse of feminism which predominantly questions gender inequality on a single axis as a fight against patriarchy, Arya and Rathore pose the important question, ‘Why Dalit Feminist Theory?’. Although the dialogue on Dalit Feminist standpoints started during the 1990s, the core of the book lies in attempting to legitimize Dalit Feminist Theory due to the ubiquity of caste question in Indian society, which cannot be overlooked in any circumstances. Thus, the book revisits the Indian Feminist discourse for feminists to critique the gatekeeping that ‘upper caste’ privileged feminists did to represent the issues of all women by homogenizing the category of a woman based on a few percentages of upper caste women leaving out Dalit, Bahujan, Adivasi and minority women who forms a much larger percentage in comparison. The book is an important read due to its critical engagement and initiation of a dialogue with Indian feminists to argue the need for Dalit Feminist Theory in reshaping Indian feminist discourse.